Experimental investigation of chip tool contact process and determination of optimum cutting speed for steel of any composition - Amin, A. K. M. Nurul; Md., Abu Hanifa (1990)
Cutting Speed is one of the most important factors on which production cost and productivity of any machining operation mainly depend. One of the reasons for high production cost of local products is the lack of technical knowhow regarding the selection of optimum cutting condition of which cutting speed is the principal parameter. One of the main source of raw materials for local mechanical parts are easily available steel scraps, whose composition in most cases are unknown and the facilities for determination of the same are inadequate and costly. For such steel scraps of unknown composition and even for imported steel of known composition it is difficult to determine the optimum cutting conditions without performing tool wear test due to the absence of information regarding optimum cutting conditions of these materials. In the present work an experimental method has been developed to determine the optimum cutting speed for a given set of values of feed and depth of cut, when cutting is performed with cemented carbide tool material of a given composition. Eliminating the lengthy and laborious method of determining composition and the conventional tool wear test for the purpose of determining optimum cutting speed, the new method presents an easy means of determining the optimum cutting speed for steel including scraps of any composition.